Price Discovery in Brazilian FX Markets - Márcio Garcia; Marcelo Medeiros; Francisco Santos (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2014)
Brazilian Foreign Exchange (FX) markets have a unique structure: most trades are conducted in the derivatives (futures) market. We study price discovery in the FX markets in Brazil and indicate which market (spot or futures) adjusts more quickly to the arrival of new information. We find that futures market dominates price discovery since it responds for 66.2% of the variation in the fundamental price shock and for 97.4% of the fundamental price composition. In a dynamic perspective, the futures market is also more efficient since, when markets are subjected to a shock in the fundamental price, it is faster to recover to equilibrium. By computing price discovery according to calendar semesters, we find evidence of the correlation between price discovery metrics and market factors, such as spot market supply-demand disequilibrium, central bank interventions and institutional investors' pressure.
Keywords: 330; price discovery; exchange rate; efficiency; arbitrage; derivatives; Brazilian economy